ANALISIS KEMAMPUAN BERNALAR KRITIS PADA CAPAIAN PEMBELAJARAN MUATAN PROFIL PELAJAR PANCASILA MATERI KONSTITUSI DAN NORMA KELAS IV SD MUHAMMADIYAH PURWODADI - Aiz Liana Salma; Muflikhul Khaq; Suyoto (LPPM STKIP Bina Bangsa Meulaboh, 2024)
This research aims to determine and analyze students' critical reasoning abilities on the learning outcomes of the Pancasila student profile content regarding the constitution and norms of class IV at SD Muhammadiyah Purwodadi. Indicators of critical reasoning abilities in research are students obtaining information and ideas, analyzing and evaluating reasoning, and reflecting on thoughts and thinking processes. The subjects of this research were 21 students in class IV Al-Majid SD Muhammadiyah Purwodadi. The object of research is students' critical reasoning abilities. This type of research is descriptive qualitative research. Data collection techniques use interview, observation, test and documentation techniques. Data collection instruments use interview guidelines, observation, and critical reasoning ability tests. The research data examination technique from Moleong (2009) uses technical triangulation and source triangulation. The data analysis used refers to Miles and Huberman (2009), namely 1) data collection; 2) data reduction; 3) data presentation; and 4) drawing conclusions. The results of this research are students' critical reasoning abilities which have been reviewed from the test results, students have critical reasoning abilities with three students in the very advanced category, seven students in the advanced category, three students in the developed category, and the undeveloped category. there are 8 people. Each student has different indicator achievements according to the results of the correct answers on the test.